THE STANDARDS THAT RULE THE INTERNAL AUDITORS OF THE INDUSTRIAL COMPANIES IN THE CITY OF BENGHAZI - Elbadry, Dr. Masoud (Dirasat in Economics and Business, 2004)
The development of the role played by internal auditors in recent years from auditing doc uments and books to controlling and evaluating all faces of internal control either financial or man agerial, had led the writer to conduct this study. The aim of this paper 1s to focus the attention on the standards that should exist to rule the function of the internal control in ass1s t1ng management to carry out its responsibilities.